Effect of tissue microenvironment on fibrous capsule formation to biomaterial-coated implants. (June 2021) - Hernandez, Jamie L.; Park, Jaehyung; Yao, Shan; Blakney, Anna K.; Nguyen, Hienschi V.; Katz, Bob H.; Jensen, Jeffrey T.; Woodrow, Kim A.
Abstract: Within tissue exposed to the systemic immune system, lymphocytes and fibroblasts act against biomaterials via the development of a fibrous capsule, known as the foreign body reaction (FBR). Inspired by the natural tolerance that the uterine cavity has to foreign bodies, our study explores the role of microenvironment across classical (subcutaneous) and immune privileged (uterine) tissues in the development of the FBR. As a model biomaterial, we used electrospun fibers loaded with sclerosing agents to provoke scar tissue growth. Additionally, we integrated these materials onto an intrauterine device as a platform for intrauterine biomaterial studies. Polyester materials in vitro achieved drug release up to 10 days, greater pro-inflammatory and pro-healing cytokine expression, and the addition of gelatin enabled greater fibroblast attachment. We observed the materials that induced the greatest FBR in the mouse, had no effect when inserted at the utero-tubal junction of non-human primates. These results suggest that the FBR varies across different tissue microenvironments, and a dampened fibrotic response exists in the uterine cavity, possibly due to immune privilege. Further study of immune privileged tissue factors on biomaterials could broaden our understanding of the FBR and inform new methods for achieving biocompatibility in vivo . Graphical abstract: Image 1 Highlights: Biomaterials examined for FBR across subcutaneous and uterine environments. Polyester fibers can achieve physicochemically diverse drug release up to 10 days. Polyester fibers induce higher pro-inflammatory and pro-healing cytokine expression. PLGA/PCL/Gel/SN initiated the greatest FBR subcutaneously in mice. Targeted fiber/IUD did not initiate scar tissue growth in a uterine NHP model.